Characterization of shortwave and longwave properties of several plastic film mulches and their impact on the surface energy balance and soil temperature. (15th January 2021) - Jones, Hughie; Black, Thomas Andrew; Jassal, Rachhpal Singh; Nesic, Zoran; Johnson, Mark Stephen; Smukler, Sean
Highlights: Methods for measuring film shortwave and longwave radiative properties are described. Plastic film mulches typically increased G, even if they were highly reflective. Plastic film mulches increased soil temperature at the 2- and 10-cm soil depths. Compared to bare soil, plastic film mulches increased the heat-sharing ratio ( G / H ). Films decreased the daily S d required for positive daily G by up to 8.2 MJ m −2 . Abstract: We used, and present, robust methodologies to measure the shortwave ( S ) and longwave ( L ) spectral radiative properties (reflectivity ( ρ ), transmissivity ( τ ) and absorptivity ( α )) of nine plastic films and quantified their effect, when used as mulches, on soil heat flux density ( G ), net radiation ( R n, above the films) and soil temperature ( T s2cm, 2-cm depth; T s10cm, 10-cm depth) in comparison to a control (bare soil). During the daytime, all treatments increased G when compared to the control to a maximum of ~45%, except for a plastic film that had a high shortwave ρ ( ρ s ) value (0.45). The films with the highest α s and ρ s values had the highest and lowest daytime R n, respectively. As a general rule, films with high τ s and α L values caused the greatest increases in G, T s2cm and T s10cm . In contrast, a comparison of three black plastic films with similarly high α s and different longwave properties showed that the film with the highest α L value achieved the lowest G and T s2cm, which was unexpected. The daytime heat-sharing ratio ( G / H, where H is sensible heat flux on the upward-facing side of the mulch) ranged in value from 0.80 ± 0.47 (mulch with τ s  = 0.79 α L  = 0.39) to 0.26 ± 0.13 (mulch with α s  = 0.96 α L  = 0.94). The lowest total daily downwelling shortwave radiation ( S d ) required for total daily G to become positive was 9.4 MJ m −2 compared to 17.6 MJ m −2 for the control, which shows the potential of plastic films for growing-season extension.